The journey to separate but equal : Madame Decuir's quest for racial justice in the Reconstruction era - Beermann, Jack M. (Lawrence, Kansas : University Press of Kansas, 2021)
"[This book] examines the tragic case of Hall v. DeCuir (1878) that helped pave the way for Plessy v. Ferguson's legitimation of the judicial doctrine and social practice of 'separate but equal' facilities. The book tells the story of the injustice done to Madame Josephine DeCuir in July 1872 aboard the Governor Allen steamship on her overnight journey up the Mississippi River from New Orleans to Point Coupee Parish. DeCuir was denied a room in the ladies' cabin due to her status as a woman of color. Nine days after the trip she filed suit against Captain John Benson, claiming that the refusal to accommodate her violated an 1869 Louisiana statute. The Supreme Court case that followed-=, in which the US Supreme Court reversed the Louisiana Supreme Court's decision, is a rich source of information about the racial attitudes in the aftermath of the Civil War, the special situation of the French-speaking people of color in Louisiana, and the post-Reconstruction 'redemption' of the South that followed the disputed election of 1876"--
Louisiana's gens de couleur and the DeCuir and Dubuclet families -- Madame DeCuir returns from France and hires new lawyers -- Madame DeCuir's journey and Reconstruction -- Madame DeCuir's suit against Captain Benson -- Judge Collum decides -- The Louisiana Supreme Court affirms -- Captain Benson takes his case to the US Supreme Court -- Louisiana (and the entire South) redeemed -- The US Supreme Court decides -- The completion of the law's journey to separate but equal.
Includes bibliographical references and index.
Online resource; title from digital title page (viewed on July 27, 2021).
JSTOR
Keywords: Decuir, Josephine -- Trials, litigation, etc; DeCuir, Josephine -- Trials, litigation, etc; Race discrimination -- Law and legislation -- United States -- History -- 19th century; Race discrimination -- Law and legislation -- Louisiana -- History -- 19th century; Equality before the law -- United States -- History -- 19th century; Equality before the law -- Louisiana -- History -- 19th century; African Americans -- Civil rights -- United States -- History -- 19th century; African Americans -- Civil rights -- Louisiana -- History -- 19th century; United States -- Race relations -- History -- 19th century; Louisiana -- Race relations -- History -- 19th century; Reconstruction (U.S. history, 1865-1877); Égalité devant la loi -- Louisiane -- Histoire -- 19e siècle.; Noirs américains -- Droits -- États-Unis -- Histoire -- 19e siècle.; Noirs américains -- Droits -- Louisiane -- Histoire -- 19e siècle.; États-Unis -- Relations raciales -- Histoire -- 19e siècle.; Louisiane -- Relations raciales -- Histoire -- 19e siècle.; Civil Rights; LAW; Constitutional; United States; HISTORY; Reconstruction (U.S. history, 1865-1877); Race relations; Race discrimination -- Law and legislation; Equality before the law; African Americans -- Civil rights; United States; Louisiana; 1800-1899; Plessy v. Ferguson, 163 U.S. 537 (1896); Electronic books; Trials, litigation, etc; History